Longterm outcome after injection sclerotherapy for oesophageal varices in children with extrahepatic portal hypertension. Issue 2 (February 1994) - Stringer, M D; Howard, E R
Abstract : A consecutive series of 36 children with bleeding from oesophageal varices secondary to extrahepatic portal hypertension was successfully treated by endoscopic injection sclerotherapy and followed up over a mean period of 8.7 years after variceal obliteration. There were no deaths from portal hypertension or its treatment and morbidity related to oesophageal sclerotherapy was minimal. Endoscopic injection sclerotherapy alone proved safe and effective in controlling variceal bleeding from portal hypertension in over 80% of the children. Recurrent variceal bleeding developed in 10 (31%) patients but half of these were effectively treated by further sclerotherapy. Gastric variceal bleeding unresponsive to sclerotherapy necessitated successful portosystemic shunt surgery in four (13%) patients. Two children required splenectomy for painful splenomegaly. In most children injection sclerotherapy is the best treatment for the primary management of bleeding oesophageal varices, reserving portosystemic shunting or other surgical procedures for those with bleeding from gastrointestinal varices.